THE EFFECT OF LIFESTYLE DISCIPLINE ON FUTSAL SPORTS ACHIEVEMENT AT STATE MIDDLE SCHOOL 2 SUNGGAL - Febtrinauli, Sarah Kristina; Damanik, Suryadi (Journal of Physical Education, Health and Sports Recreation, 2025)
This study examines the relationship between a disciplined lifestyle and futsal performance among students at Sunggal 2 Public Junior High School. This study highlights the importance of structured habits, such as adherence to schedules, a healthy diet, and physical fitness, as factors supporting success in sports. Using a quantitative correlational method, data were collected through questionnaires distributed to ten students aged 14–16 who actively participate in extracurricular futsal activities. The results show a significant positive relationship between a disciplined lifestyle and futsal performance, with discipline contributing to physical readiness and tournament success. This study emphasizes the important role of a disciplined lifestyle in supporting sporting excellence and provides insights for educators and coaches to improve student sporting performance through fostering a structured lifestyle. This is demonstrated by a significance value of 0.042 <0.05.